Interleaved tapped-inductor boost converter for higher power and voltage gain applications - Ramos, Niño Christopher B. (2013)
In this paper, an interleaved tapped-inductor boost converter (ITBC) was proposed as a candidate for applications requiring higher power and voltage gain. Design equations for the converter were presented along with the selection of major components. Power loss and efficiency analysis was carried out by MATLAB simulations. SIMetrix open-loop model was generated for further design verification and analysis. Experimental validation was then performed by implementing the corresponding hardware prototype. Hardware open-loop test was first performed followed by integrated closed loop test to ensure the readiness of the converter for interleaved operation. Performance was analyzed in terms of efficiency, thermal management and load and line regulation. Experimental results showed significant resemblance to the MATLAB and SIMetrix simulations. Full-load efficiencies of 88.5%, 92.6% and 93.1% were obtained for 50V, 100V, and 150V input respectively during integrated closed loop test. Line regulation of 8.84x10-4 and load regulation of 6.36x10-3 obtained simultaneously during integrated closed loop test indicate a good performance for the converter. By being able to implement the hardware, test it and compare the results with the software simulations, the interleaved-tapped inductor boost converter has been shown to be valid candidate for higher power and voltage gain applications
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman
Keywords: Electric current converters; Switching power supplies; Interleaved tapped-inductor boost converter (ITBC.; MATLAB simulations; Continuous conduction mode (CCM.